DISSECTING THE RELATIONSHIP BETWEEN CORPORATE SOCIALRESPONSIBILITY AND CORPORATE INNOVATION: A LITERATURE STUDY - Iman Hikmat Nugraha (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2024)
This study explores the relationship between Corporate Social Responsibility (CSR) and corporate innovation through a comprehensive literature review. Various studies show that CSR can stimulate innovation by creating a positive image, increasing customer loyalty, and opening up new market opportunities. Companies active in CSR often discover social needs that require innovative solutions, resulting in synergies between social goals and business benefits. However, studies also reveal the potential negative impact of CSR on innovation. Allocation of significant resources to CSR can reduce investment in research and development (R&D), while compliance with CSR standards can add bureaucratic complexity and hamper corporate flexibility. In conclusion, the relationship between CSR and innovation is two-way and requires strategic balancing. Thoughtful design and execution of CSR is essential to maximise the benefits while minimising the negative impact on a firm's innovation process.